Chronic Pain Experience and Management among People Who Use Illicit Drugs: A Qualitative Study in Montreal (QC) - Lise Dassieu; Jean-Luc Kaboré; Manon Choinière; Élise Roy (Taylor & Francis Group, 2019)
Introduction/Aim: Chronic non-cancer pain (CNCP) is both highly prevalent and undertreated among people who use illicit drugs (PWUD). To address the current opioid crisis, several health authorities have produced guidelines recommending not to prescribe opioid painkillers to patients with substance abuse risk factors. This could jeopardize pain relief for PWUD suffering from CNCP. This study aims to describe: (1) PWUD's daily CNCP experiences; (2) barriers of access to adequate CNCP management for PWUD in the opioid crisis context; (3) PWUD's stated needs for improving their CNCP and healthcare experiences. Methods: This was a qualitative study. In-depth semi-structured interviews were conducted with 25 PWUD (illicit opioids and/or cocaine) suffering from CNCP (≥ 3 months) recruited in downtown Montreal (2017/07 to 2018/05). Interviews were analyzed using Grounded Theory method. Results: Participants faced multiple health problems (e.g. HIV, hepatitis C) and social issues (e.g. homelessness, precarious employment) concomitantly with CNCP and substance use. These problems contributed to heighten their pain intensity. Physicians' increased defiance against PWUD in the opioid crisis context led to major barriers for participants' pain management. Participants experienced stigma and discrimination in the healthcare system. They wished they could access non-pharmacological therapies (e.g. physiotherapy) as alternatives to opioids, but these therapies were unaffordable. Some participants reported self-medicating their CNCP with street drugs when no other solution was available. Discussion/Conclusions: PWUD suffering from CNCP are a population with several comorbidities and high health care needs. Public policies should be revisited to improve access to appropriate CNCP management for this population.